Pengaruh Iklan dan Promosi Penjualan Terhadap Keputusan Pembelian Demochist Clothing - Leonandri, Dino Gustaf; Erpurini, Wala (Jurnal EMT KITA, 2024)
Demochist Clothing Bandung consumers are the subjects of this research. The aim of this research is to find out how much influence advertising and sales promotions have on consumer purchasing decisions at Demochist Clothing Bandung, both partially and simultaneously. This research uses descriptive and associative methods. Multiple linear regression analysis is used as the analysis method. Apart from that, the research instruments were also tested for validity and reliability. The research results show that exogenous variables (advertising and sales promotions) influence endogenous variables (purchasing decisions) both partially and simultaneously. This study shows that Demochist Clothing Bandung can re-evaluate the suitability of advertising to improve consumer purchasing decisions.